THE EFFECT OF JOB PLACEMENT AND WORK ENVIRONMENT ON EMPLOYEE LOYALTY: EVIDENCE FROM PT KERETA API INDONESIA (PERSERO) REGIONAL DIVISION III PALEMBANG - Henny Aprillia; Heriyanto Heriyanto (Universitas Nusa Cendana, 2026)
Employee loyalty constitutes a critical foundation for the operational sustainability of PT Kereta Api Indonesia (Persero) Regional Division III Palembang, particularly amid the increasing intensity of passenger and freight transportation services. This study aims to examine the influence of job placement and work environment on employee loyalty, both partially and simultaneously. A quantitative method with a causal-associative design was employed. The research population comprised 176 permanent employees, with a sample of 64 respondents determined using Slovin’s formula with a 10% margin of error. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression. The results indicate that job placement has a significant effect on employee loyalty, and the work environment also significantly influences employee loyalty. Furthermore, both variables simultaneously have a significant impact on employee loyalty. These findings highlight that appropriate job placement aligned with employee competencies, along with a supportive and conducive work environment, are strategic factors in strengthening employee loyalty and ensuring the sustainability of organizational performance. Keywords: Job Placement; Work Environment; Employee Loyalty; PT KAI Regional Division III Palembang